2013
DOI: 10.1161/circgenetics.113.000022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inherited Genetic Variants Associated With Lipid Profile, Hypertension, and Coronary Artery Disease on the Risk of Intracranial and Abdominal Aortic Aneurysms

Abstract: Background— Epidemiological studies show that an unfavorable lipid profile and coronary artery disease (CAD) are risk traits for abdominal aortic aneurysms (AAAs) but not for intracranial aneurysms (IAs), and that hypertension is a main risk trait for IAs but not for AAAs. To evaluate these observations, we investigated single-nucleotide polymorphisms associated with serum lipid levels, hypertension, and CAD and tested their contribution to AAA and IA risk. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 45 publications
2
16
0
1
Order By: Relevance
“…A variety of genes or chromosomal regions have been identified in both familial and sporadic cases of IAs. [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] In linkage studies, regions on chromosomes 1p34.3-p36.13, 7q11, 19q13.3, and Xp22 have been associated with IAs. Genome-wide association studies identified replicated associations on chromosome 4q31.23 (EDNRA), 8q12.1 (SOX17), 9p213 (CDKN2A/CDKN2B/CDKN2BAS), 10q24.32 (CNNM2), 12q22, 13q13.1 (KL/STARD13), 18q11.2 (RBBP8), and 20p12.1, with the strongest evidence for the CDKN2BAS and SOX17 genes.…”
Section: Family History and Geneticsmentioning
confidence: 99%
“…A variety of genes or chromosomal regions have been identified in both familial and sporadic cases of IAs. [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] In linkage studies, regions on chromosomes 1p34.3-p36.13, 7q11, 19q13.3, and Xp22 have been associated with IAs. Genome-wide association studies identified replicated associations on chromosome 4q31.23 (EDNRA), 8q12.1 (SOX17), 9p213 (CDKN2A/CDKN2B/CDKN2BAS), 10q24.32 (CNNM2), 12q22, 13q13.1 (KL/STARD13), 18q11.2 (RBBP8), and 20p12.1, with the strongest evidence for the CDKN2BAS and SOX17 genes.…”
Section: Family History and Geneticsmentioning
confidence: 99%
“…[41, 45] Polygenic risk scores incorporating variants associated with LDL cholesterol and CAD have also been linked to abdominal aneurysms, confirming links between these disorders. [46] For thoracic aortic disease, the gene encoding fibrillin-1 has been associated with risk and is the same gene in which loss-of-function mutations cause Marfan’s syndrome, characterized by thoracic aortic disease as well as other arteries. Fibrillin-1 is an extracellular matrix protein which anchors smooth muscle cells to the extracellular matrix, mutations in which are considered to disrupt mechanosensing and signaling in the aortic wall.…”
Section: Vascular Traitsmentioning
confidence: 99%
“…1 The etiology of CA involves hemodynamic stress and inflammation, with similarities and important differences to abdominal aortic aneurysms (AAA). 14 Treatment for both unruptured and ruptured CA is surgical, with coiling and clipping to prevent rupture and re-rupture; there is no pharmacological treatment. 5,6 …”
Section: Introductionmentioning
confidence: 99%